PERANAN MEDIA SOSIAL INSTAGRAM DALAM MENINGKATKAN KUNJUNGAN OBYEK WISATA KULINER - Susanna Silvia Sembiring; Williandani, Mega; Girsang, Dameria (Jurnal Ilmiah Akomodasi Agung, 2023)
Instagram social media is a social networking site like a web-based service that allows anyone to build a public profile within a limited system. Social media not only includes a variety of new media platforms but also combines several other social media systems such as Facebook, Tik-Tok, Twitter and others. Tourism object is an object which means shape and tourism which means facilities related to that shape, which can attract visitors or tourists to come to the object. This type of research is Qualitative research, in this writing, those who have been determined as subjects/informants of writing are 7 (seven) people. The data collection techniques used are field research, documentation, interviews, observation. The obstacles faced in increasing tourist visits using social media are the lack of creativity of human resources at the tourist attraction. And also there is still a lack of photo spots for tourists at Culinary Tourism Objects. Efforts to overcome the obstacles faced by culinary tourism objects in increasing visits to culinary tourism objects through Instagram social media are to improve promotional media, provide guidance or training to workers to provide better service and create a unique feature of the object.